Analisis briket fiber mesocarp kelapa sawit metode karbonisasi dengan perekat tepung tapioka - Istianto Budhi Rahardja; Cenda E Hasibuan; Yudi Dermawan (University of Muhammadiyah Jakarta, 2022)
This research aims to develop solid waste produced by oil palm plantation processing in the form of palm oil mesocarp fiber. Utilization which is usually only as boiler fuel in a Palm Oil Mill. Utilization of mesocarp fiber waste is to reduce waste, has a large heating value, and has a selling value. In the process of making mesocarp fiber briquettes, raw materials are provided, drying, charcoal (carbonization), filtering, forming 100 gr of charcoal with 150 ml, 200 ml, 300 ml of water solvent with tapioca starch adhesive (50 gr), and drying. The results of this research were briquettes with 150 ml solvent with a water content of 7.6%, an ash content of 22.52%, a burning time of 143 minutes, a burn rate of 0.21 %. The 200 ml solvent, namely: water content of 5.7%, ash content of 11.28%, burning time of 77 minutes, burning rate of 0.38 %. And in the 300 ml solvent, namely: water content of 5.2%, ash content of 16.84%, burning time of 67 minutes, burning rate of 0.36 %.